Female entrepreneurs in nature-based businesses: working conditions, well-being, and everyday life situation. (28th July 2017) - Sörensson, Anna; Dalborg, Cecilia
ABSTRACT: Nature-based businesses – such as those involving the land, forest, garden, or rural environment – are industries with significant growth potential. Female entrepreneurs within nature-based businesses are often invisible in statistics, as well as in research, since traditionally men have owned such companies. This had led to a lack of knowledge about the opportunities for women to start and run nature-based businesses. The aim of this paper was to explore the ambition, working conditions, and life situation for female entrepreneurs within nature-based businesses in sparsely populated areas of Sweden. Interviews were carried out with 18 female entrepreneurs within nature-based businesses in Sweden. One conclusion that was drawn from this study is that women within this industry are mainly pulled into entrepreneurship, that is, the entrepreneurship is opportunity based. Four different types of entrepreneurs were identified based on their ambitions when it comes to time spent in business and the degree of innovation. This study shows that it is often difficult to achieve profitability in a company, and the female entrepreneurs highlight that that self-employment implies hard but rewarding work. The findings of this study can be used by public actors in the design of support systems for female entrepreneurs in nature-based businesses.